Accentuating the right to ample access to quality education in rural South Africa : legal analysis - Sefoka, Isaiah Mmatipe (My University, 2016)
This mini dissertation seeks to articulate the issues and challenges being faced by the rural South Africa pertaining to the aspect of providing ample access to quality education. The structures, policies and programs of the flows of apartheid are therefore compered and contrasted to the post-apartheid (1994) structures, policies and programmes. It further argues that any impediment to the right is in contrast to the spirit and purport of the provisions of the Bill of Rights enshrined in the South African Constitution of 1996 which provides for this constitutional right. Although there was a radical transition in educational policies and programmes from apartheid to postapartheid, till to date there are still numerous challenges within the basic and higher educational sectors within and between institutions. This mini dissertation recommends that government should make education completely free from levels such as primary, tertiary and the postgraduate levels, and to use education as an investment tool. In this regard, government will be investing in youth to contribute in developing solutions to aid the rural masses. It recommends that education be made compulsory from grade 1 to grade 12.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Quality education; Constitutional rights; Rural education; Right to education -- South Africa; Education -- South Africa; Educational law and legislation; Education, Rural -- South Africa